Cognitive and brain micro-structural correlates of alexithymia in essential tremor patients. - Corakci, Z; Tantik, Pak; Otcu, H; Sengul, HS; ÇORAKÇI, ZEYNEP; Sengul, Y; Alkan, ALPAY; ALKAN, ALPAY (My University, 2020)
Essential tremor (ET) is the most common movement disorder which has both motor and non-motor findings such as neuropsychiatic symptoms. Alexithymia is defined as inability to identify and describe emotions experienced by one-s self or others. In our study, we aimed to evaluate the neurocognitive and brain micro-structural correlates of alexithymia in ET. 40 ET patients (mean age = 53.05 +/- 19.74 years), were included. Fahn-Tolosa-Marin Tremor Rating Scale, Toronto Alexithymia Scale (TAS), Beck Depression Inventory, Beck Anxiety Inventory and detailed neurocognitive evaluation were applied to all patients. The patients were divided into three groups based on their TAS scores: no alexithymia, probable alexithymia, definite alexithymia. Diffusion Tensor Imaging (DTI) was performed in all patients. The mean TAS score was 50.05 +/- 10.06. Depressive symptoms and anxiety levels were higher in definite alexithymia (p < 0.001,p < 0.01). Partial correlation controlling for age, gender and educational level between alexithymia scores and each cognitive test showed significant association between similarities (p < 0.001) and phonemic verbal fluency (p = 0.04). Left orbitofrontal cortex average diffusion coefficient (ADC) value (p = 0.05), left anterior cingulate cortex fractional anisotropy (FA) value (p = 0.04), right cuneus FA value (p = 0.04), left amygdala ADC value (p = 0.01) and left insula ADC value (p = 0.02) were differed between groups. TAS and DTImetrics were not found to be independently associated with the level of anxiety (p < 0.001) and depressive symptoms (p < 0.01). As a conclusion, impairments in executive function and complex attention were correlated with higher levels of alexithymia in ET. Many micro-structural alterations were determined to be correlated with alexithymia levels.